Pretreatment and hydrolysis processes on synechococcus Pcc 7002 cells for glucose production - Saleh, Noraini; Azmi, Azlin Suhaida; Amid, Azura; Halmi Shari, Ummi Syuhada (AENSI Publications, 2014)
Microalgae are potential alternative source for ren ewable energy such as bioethanol. To produce bioethanol pretreatment methods such as son ication and acid hydrolysis for carbohydrate production are required. Pretreatment is important to release the carbohydrate from the microalgae cell wall as well as to increase the production. These processes were applied to Synechococcus PCC 7002, a type of cyanobacteria species. The aim of this project was to release the glucose from cyanobacteria cells prior to bioethanol production. Three parameters were studie d which were sonication time (15, 30 and 45 minutes), sulphuric acid concentration (1 %, 3%, 5% and 7% v/v) and hydrolysis time (15 and 30 minutes). The response s tudied was carbohydrate yield. The result showed that, most of the samples with 15 min utes of sonication gave higher carbohydrate content compared to 30 and 45 minutes. In contrast to that, highest concentration of sulphuric acid at 7% and longer hydrolysis duration at 30 minutes hydrolysis gave higher yield of carbohydrate. It was concluded that neither glucose nor sucrose yields from sonicated and hydrolyzed biomass. This could be due to insufficient of heat to break the glycosidic linkage between the oligosaccharide.